Do the Hydatid Cysts Have Unusual Localization and Dissemination Ways in the Chest Cavity? - Yucel Akkas; Tevfik Kaplan; Neslihan Gulay Peri; Bulent Kocer (Case Reports in Surgery)
We wanted to report our two cases of intrathoracic extrapulmonary hydatid cyst in pleural cavity due to its rarity. Our first case is a 24-year-old male patient who was admitted with a cystic mass lesion consistent with hydatid cyst which was incidentally detected in inferior lobe of the right lung neighboring to thoracic wall and diaphragm. Our second case is a 32-year-old male patient who was admitted with chest pain and a cystic lesion in apex of the right hemithorax and intercostal field in basal after he had been medically treated due to hydatid cyst of the dome of the liver for two years. The cysts were removed with thoracotomy. Extrapulmonary intrathoracic hydatid cysts were evaluated with regard to invasion ways and treatment indications and methods.